Coercividade de nanopartículas de CoFe2O4 dispersas em uma matriz de SiO2 - Costa, Maria Helena Carvalho da (2015)
In this work, we study the magnetic properties of CoFe2O4 nanoparticles dispersed in silica (SiO2) matrix. Samples were produced by the sol-gel method and synthesized at different temperatures. The average distance between the particles and thus the nature of inter-particle interactions were controlled for using different concentrations of iron and cobalt salts and the starting material tetraethylorthosilicate (TEOS). The samples were characterized by thermogravimetry (TG), X-ray fluorescence (XRF), X-ray diffraction (XRD), transmission electron microscopy (TEM) and magnetization as a function of magnetic field and temperature. Thermogravimetric analysis showed that the weight loss increases with increasing concentration of salts in the starting solution. The results of X-ray diffraction combined with the transmission electron microscope images confirmed the presence of CoFe2O4 nanoparticles dispersed into the SiO2 matrix. Magnetization measurements showed a typical behavior generally showed by a magnetic nanoparticles system, that is, the observation of a peak in the curve FC-ZFC with a thermal hysteresis in the low temperature region. In particular, we observed a dependence of the coercive field with temperature of CoFe2O4 nanoparticles that did not follow the predictions of the model Bean-Livingston. We believe that this fact is linked more to the effect of size distribution than the possible effects of interaction between the nanoparticles. In this regard, a model considering a particle size distribution in the coercivity of nanoparticles was used. The model was able to fit the experimental data to wide temperature range.